Theoretical Analysis of Offenses: Economic Approach (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The article deals with theoretical aspects of the offenses according to economic approach. The aim of the article is the analysis of the main theoretical and methodological positions of the economic theory of offenses in the context of their application to the shadow economy. The basic methodological preconditions and principles of neo-classical and neo-institutionalism theory by G. Becker are analyzed. The motives of limited rationality of behavior when the economic agents select illegal behavior are shown. The advantages of monetary rationality in the applied aspect for hidden sector of the shadow economy in comparison with illegal ones are defined. A general modified interpretation of mathematical formula of the expected utility of any offenses is presented. The problem of offenses «self-sufficiency» under risk is defined. Wide possibilities of economic theory of offenses and its objective disadvantages are grounded. It is proved that the key factor of shadow economy deterrence is the probability of detecting offenses and their punishment.
Keywords: offense, shadow economy, rationality, the probability of detecting, punishment, hidden economy